Pengaruh Komitmen Organisasional Dan Stres Kerja Terhadap Kinerja Dosen Tetap Fakultas Ilmu Sosial Dan Politik Universitas Maritim Raja Ali Haji Tahun 2014 - Hendrayady, Agus; pangestoeti, wahjoe; Darosa, Herayni (Jurnal Ilmu Administrasi Negara (JUAN), 2015)
Herayni Darosa Agus Hendrayady Wahjoe Pangestoeti(agushendrayady05081973@gmail.com) (Jurusan Ilmu Administrasi Negara FISIP UMRAH) Abstract: The purpose of this study was to analyze either simultaneously and partially influence organizational commitment and job stress on the tenured lecturer’s performance in Faculty of Social and Political University Maritim Raja Ali Haji. And this study is a survey to address the three main hypotheses, which alleged that: (1) suggested that organizational commitment and job stress together have a significant impact on the performance of tenured lecturers; (2) suggested that organizational commitment has a significant influence performance of tenured lecturers; (3)suggested that job stress has a significant effect on the performance of tenured lecturers. The subjects on this study is lectures in Faculty of Social and Political University Maritim Raja Ali Haji. The tenured lecturers in question is the duty as lecturing and have a minimum term of one point five year. The method of analysis used in this study is a multiple linear regression. The data used in this study are primary and secondary data obtained through literature studies, and distributing questionnaires to 26 respondents. The results of this study state that organizational commitment and job stress also simultaneously have a significant impact on lecturer’s performance by 50,7 %. And organizational commitment is partially significant influence on lecturer’s performance by 39,6 % and partially job stress had no significant effect on lecturer’s performance by 11,1 %. In conclusion, this study proves that organizational commitment and job stress jointly affect the performance of lecturers in Faculty of Social and Political University Maritim Raja Ali Haji.